2021
DOI: 10.1186/s12974-021-02161-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute inflammatory profiles differ with sex and age after spinal cord injury

Abstract: Background Sex and age are emerging as influential variables that affect spinal cord injury (SCI) recovery. Despite a changing demographic towards older age at the time of SCI, the effects of sex or age on inflammation remain to be elucidated. This study determined the sex- and age-dependency of the innate immune response acutely after SCI. Methods Male and female mice of ages 4- and 14-month-old received T9 contusion SCI and the proportion of micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 50 publications
(100 reference statements)
1
48
0
Order By: Relevance
“…A recent study by Stewart et al [ 83 ] supported the inflammation after SCI is sex-dependent both at the level of cellular recruitment and phenotype, effects of aging, however, while present, were overall less pronounced. Interestingly though, Tnf expression was one of the genes that differed between 4-month-old and 14-month-old SCI mice, whereas sex did not appear to affect Tnf expression [ 83 ]. How the temporal and cellular expression of TNF changes with age and sex after SCI remains to be elucidated.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A recent study by Stewart et al [ 83 ] supported the inflammation after SCI is sex-dependent both at the level of cellular recruitment and phenotype, effects of aging, however, while present, were overall less pronounced. Interestingly though, Tnf expression was one of the genes that differed between 4-month-old and 14-month-old SCI mice, whereas sex did not appear to affect Tnf expression [ 83 ]. How the temporal and cellular expression of TNF changes with age and sex after SCI remains to be elucidated.…”
Section: Discussionmentioning
confidence: 95%
“…A limitation of the present study is that only female mice were used. The acute inflammatory profile has been demonstrated to differ between female and male mice [ 83 , 84 ]. Additionally, the inhibition of TNF-TNFR1 signaling has been demonstrated to be therapeutic for neuropathic pain in males but not in females [ 85 ], highlighting the importance of incorporating both male and female groups in future SCI research to account for sexual dimorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…According to epidemiology of traumatic SCI either in US or in China, the incidence rate in males is four or five times higher than female [ 57 , 58 ], and there is a difference in the recovery between sex in both rat models and human beings in clinic [ 59 ]. There is emerging evidence that sex and age are important variables that affect SCI recovery, including on the acute inflammatory response [ 60 ]. Therefore, to further push the translation of nafamostat on SCI, more preclinical experiments should be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Although more than 80% of patients are men aged approximately 30 years old [ 65 ], some reports have shown that female rodents may have better outcomes than male rodents after SCI [ 66 , 67 ]. A recent study showed stronger total inflammation and more microglia at the lesion epicenter in SCI male rats than in SCI female rats, while the number of macrophages in the damaged area was higher in SCI female rats [ 68 ]. Considering that PBM in our study inhibited the activation of total Iba1 + cells indiscriminately, we predict that the therapeutic effects of PBM can be reproduced in female rat models of SCI without changing the overall conclusions, although this requires confirmation in the future.…”
Section: Discussionmentioning
confidence: 99%